Health and nutrition effects of commercialization of agriculture - Kennedy, Eileen T. (International Food Policy Research Institute, 1994)
One of the most contentious issues in the cash crop/food crop debate revolves around the impact of commercialization of agriculture on the health and nutritional status of women and children/ This chaper examines the effects of commercialization of agriculture on preschoolers' health nad nutritional status. The chapter also assesses the effects on women along the lines of the conceptual ramework described in chapter 2.